Identifying an effective mobile health application for the self-management of allergic rhinitis and asthma in Australia. (2nd October 2020) - Tan, Rachel; Cvetkovski, Biljana; Kritikos, Vicky; O'Hehir, Robyn E.; Lourenço, Olga; Bousquet, Jean; Bosnic-Anticevich, Sinthia
Abstract: Objective: People with allergic rhinitis (AR) often self-manage in the community pharmacy setting without consulting health care professionals and trivialize their comorbidities such as asthma. A mobile health application (mHealth app) with a self-monitoring and medication adherence system can assist with the appropriate self-management of AR and asthma. This study aimed to identify an app effective for the self-management of AR and/or asthma. Methods: MHealth apps retrieved from the Australian Apple App Store and Android Google Play Store were included in this study if they were developed for self-management of AR and/or asthma; in English language; free of charge for the full version; and accessible to users of the mHealth app. The mHealth app quality was evaluated on three domains using a two-stage process. In Stage 1, the apps were ranked along Domain 1 (Accessibility in both app stores). In Stage 2, the apps with Stage 1, maximum score were ranked along Domain 2 (alignment with theoretical principles of the self-management of AR and/or asthma) and Domain 3 (usability of the mHealth app using Mobile App Rating Scale instrument). Results: Of the 418 apps retrieved, 31 were evaluated in Stage 1 and 16 in Stage 2. The MASK-air achieved the highest mean rank and covered all self-management principles except the doctor's appointment reminder and scored a total MARS mean score of 0.91/1. Conclusions: MASK-air is ranked most highly across the assessment domains for the self-management of both AR and coexisting asthma. This mHealth app covers the majority of the self-management principles and is highly engaging.